Soya food intake and risk of endometrial cancer among Chinese women in Shanghai: population based case-control study - Xu, Wang Hong (BMJ Publishing Group Ltd., 2004)
Objective To evaluate the association of intake of soya food, a rich source of phytoestrogens, with the risk of endometrial cancer. Design Population based case-control study, with detailed information on usual soya food intake over the past five years collected by face to face interview using a food frequency questionnaire. Setting Urban Shanghai, China. Participants 832 incident cases of endometrial cancer in women aged of 30 to 69 years diagnosed during 1997-2001 and identified from the Shanghai Cancer Registry; 846 control women frequency matched to cases on age and randomly selected from the Shanghai Residential Registry. Main outcome measures Odds ratios for risk of endometrial cancer in women with different intakes of soya foods. Results Regular consumption of soya foods, measured as amount of either soya protein or soya isoflavones, was inversely associated with the risk of endometrial cancer. Compared with women with the lowest quarter of intake, the adjusted odds ratio of endometrial cancer was reduced from 0.93 to 0.85 and 0.67 with increasing quarter of soya protein intake (P for trend 0.01). A similar inverse association was observed for soya isoflavones and soya fibre intake. The inverse association seemed to be more pronounced among women with high body mass index and waist:hip ratio. Conclusion Regular intake of soya foods is associated with a reduced risk of endometrial cancer.